Antihypercholesterolemic Effects of Beet (Beta vulgaris L.) Root Waste Extract on Hypercholesterolemic Rats and its Antioxidant Potential Properties - Rabeh, M. Naeem; Ibrahim, E. Marwa (Pakistan Journal of Nutrition, 2014)
The methanolic extract of beet (Beta vulgaris L.) root waste was investigated for its possible antihypercholesterolemic in cholesterol rich diet-induced hypercholesterolemia in male adult albino rats and its antioxidant potential. Different in vitro assays used for determining antioxidant potential of extracts of pulp wastes were: 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and total antioxidant capacity. Thirty five adult male albino rats were randomly divided into two main groups, the first main group (control negative: 7 rats each) fed on basal diet only, while the second main group (28 rat) fed on hypercholesterolemic diet (basal diet, 1% cholesterol, 0.25% bile salt and 15% beef tallow) for 1 month to raise the lipid profile level. After that, these hypercholesterolemic rats divided into four subgroups as follow: the first subgroup (control positive) fed on hypercholesterolemic diet only, while the other three subgroups fed on hypercholesterolemic diet and administered orally with beet root waste extract (BRWE) at a dose of 200, 400 and 600 mg/kg/day, respectively. Lipid profile was measured in serum of rats. The results indicated that, administration with extract of beet root waste at the doses of 200, 400 and 600 mg/kg b.w for 30 day showed a significant (p